ADAPTIVE CLOTHING FOR MILITARY SERVANTS WITH INJURED LIMBS:FOREIGN AND DOMESTIC EXPERIENCE - KRASNIUK, LARYSA; LUSCHEVSKA, OLENA; TROYAN, OLEKSANDR; BUKHANTSOVA, LIUDMYLA; DITKOVSKA, OLESYA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article examines the evolution of adaptive fashion, tracing its development from inception to modern technological advancements. It demonstrates that adaptive clothing is a fusion of functionality, innovation, and style, surpassing traditional clothing in its properties. Today, a devastating war is ongoing in Ukraine, resulting in many military personnel and civilians being injured and in need of medical care and rehabilitation. The increasing number of daily wounded intensifies the urgency of providing them with high-quality adaptive clothing that improves their quality of life during treatment and rehabilitation. Unfortunately, few manufacturers in Ukraine are dedicated to producing adaptive clothing, often overlooking doctors' requirements, patients' preferences, and contemporary innovations in development. Therefore, the research topic focused on designing adaptive clothing for military personnel with injured limbs is highly relevant. The absence of suitable clothing can hinder the successful treatment and rehabilitation of the wounded, potentially decreasing self-esteem and leading to social isolation. Adaptive design can address these issues by offering functional, practical, comfortable, and aesthetically pleasing clothing that aligns with user preferences and enhances quality of life throughout treatment and rehabilitation, fostering greater participation in social and professional activities. The aim of this work is to introduce the concept of designing adaptive clothing for individuals with disabilities, alongside developing and manufacturing an experimental batch of adaptive men' s shoulder and waist clothing for military personnel with injured limbs. Considering the analysis of relevant literature and patents outlining real technical solutions in adaptive clothing development, the authors have identified key characteristics of this clothing' s design. A key task of the study was to create an experimental batch of men' s adaptive clothing for military personnel with injured limbs. This clothing features adjustable openings with Velcro fasteners, enabling it to be tailored to various needs, shapes, and sizes of the body, thus creating an adaptive design that caters to a wide range of requirements for individuals with injured limbs.
Keywords: adaptive design; adaptive products; inclusive fashion; people with disabilities; functionality; accessibility; innovation